Antisecretory and antimotility activity of Aconitum heterophyllum and its significance in treatment of diarrhea - Prasad S.K.; Jain D.; Patel D.K.; Sahu A.N.; Hemalatha S. (My University, 2025)
Aim: The roots of the plant Aconitum heterophyllum (EAH) are traditionally used for curing hysteria, throat infection, dyspepsia, abdominal pain, diabetes, and diarrhea. Therefore, the present study was undertaken to determine the mechanism involved in the anti-diarrheal activity of roots of A. heterophyllum. Materials and Methods: Ant-diarrheal activity of ethanol extract at 50, 100, and 200 mg/kg p.o. was evaluated using fecal excretion and castor oil-induced diarrhea models, while optimized dose, that is, 100 mg/kg p.o. was further subjected to small intestinal transit, intestinal fluids accumulation, PGE 2-induced enteropooling and gastric emptying test. To elucidate the probable mechanism, various biochemical parameters and Na+, K + concentration in intestinal fluids were also determined. Further, antibacterial activity of extract along with its standardization using aconitine as a marker with the help of HPLC was carried out. Results: The results depicted a significant (P < 0.05) reduction in normal fecal output at 100 and 200 mg/kg p.o. of extract after 5th and 7th h of treatment. Castor oil-induced diarrhea model demonstrated a ceiling effect at 100 mg/kg p.o. with a protection of 60.185% from diarrhea. EAH at 100 mg/kg p.o. also showed significant activity in small intestinal transit, fluid accumulation, and PGE2-induced enteropooling models, which also restored the altered biochemical parameters and prevented Na+ and K+ loss. The extract with 0.0833% w/w of aconitine depicted a potential antibacterial activity of extract against microbes implicated in diarrhea. Conclusion: The study concluded antisecretory and antimotility effect of A. heterophyllum, which mediates through nitric oxide path way.